Effects of vermicompost and plant growth regulators on the growth and yield of java tea (Orthosiphon stamineus Benth.) - Fan, Li Ying (2011)
The effects of vermicompost and plant growth regulators (PGRs), which are indole-3 butyric acid (IBA) and naphthalene acetic acid (NAA), on the growth and yield of Java tea (Orthosiphon stamineus Benth.) were studied in the Agro Park of University Malaysia Kelantan (UMK). The results had shown that there was significant effect of vermicompost on the growth of Java tea; however the effect of plant growth regulators was significant only on two variables which are the number of leaf and branch. Statistical analysis showed that the interaction between vermicompost and plant growth regulators was not consistent during the observation period. Applying 400 grams of vermicompost was found to be the best for plant growth on all variables including leaves, branches, plant height, stem girth, flowering and the length of root. The highest total leaf area (TLA) of Orthosiphon stamineus also came from samples receiving the same amount of vermicompost.